IDENTIFIKASI NON VALUE ADDED ACTIVITY MELALUI ACTIVITY-BASED MANAGEMENT UNTUK MENINGKATKAN EFISIENSI HOTEL TRAVELLO MANADO - Daleno, Irna Prisye; Saerang, David Paul Elia; Elim, Inggriani (Universitas Sam Ratulangi, 2013)
Faced with the globalization era filled with fierce competition, companies must be able to improve the performance and adaptability to the existing environment to be able to continue to compete. The rivalry does not happen in manufacture industry environmentbut also in service industry, with increasing the competition in service industry especially in hotel, so Travello Hotel should create a competitive excellence. Therefore to create that excellence,Â Travello Hotel should has efficiency with the way to manage the activity without cutdown the quality of service that give to customer. This method use to manage the activity, so that create this efficiency is calledActivity-Based Management.The research has done in room division of Manado Travello Hotel. The research is descriptive which analyze to all activity in room division ofÂ TravelloÂ Hotel and classify that activity to be value added activity and non value added activity. The value added activity will be eliminated or combined with the other activity that is similar, so that the value added non cost appear from this activity could reduced the amount. The data that used in this research is quantitative as cost report in room division in Travello Hotel tahun 2012 and the qualitative data is like tool from the Hotel.The conclusion this research is to apply the method of activity-basedManagement, Travello Hotel reduces the non value added cost so it can create afficiency without cutdown the quality of service the given from Travello Hotel to customer, with using the activity-based management,the totally of expense in room division are decreases as much as Rp. 176.226.624,08 from Rp. 3.576.508.933,00 to be Rp. 3.400.282.308,92.